A new species of Hydrogamasellus (Acari: Mesostigmata: Ologamasidae) from Brazil, with a key to the world species of the genus - Santos, Jandir C.; Castilho, Raphael C.; Silva, Edmilson S.; de Moraes, Gilberto J. (Zootaxa, 2013)
Hydrogamasellus alagoensis n. sp. is described based on the morphology of adult females and males collected from litter in the State of Alagoas, Brazil. Six new combinations are proposed, namely Acugamasus avium (Karg, 1976) n. comb., Ologamasus lanceolatus (Karg, 1976) n. comb., Ologamasus microcrinis (Karg, 1979) n. comb., Ologamasus testudinis (Karg, 1976) n. comb., Rykellus longopilus (Karg, 1976) n. comb. and Rykellus ubatubaensis (Hirschmann, 1966) n. comb., and a key for the separation of females of the eighteen recognizable world Hydrogamasellus species is provided.